Determinants of macroeconomic variables on islamic stock index: evidence from frontier market / Noor Hafizha Muhamad Yusuf …[et al.] - Muhamad Yusuf, Noor Hafizha; Muhamad Hilmi, Natasha Aliana; Mohd Abdoh, Wan Mohd Yaseer; Shekh Zain, Rozihanim; Badri Shah, Noor Sharida (Universiti Teknologi MARA Shah Alam, 2020)
This paper provides useful insights on the determinants of macroeconomic variables on Islamic stock index evidence from frontier market. The aims of this study is to examine the effect of macroeconomic variables namely gross domestic product (GDP), inflation (consumer price index), exchange rate (USD exchange rate), oil price (crude palm oil) and money supply (M2) on frontier market Islamic index (FMII). This study employs Fixed Effect (FE) model of 17 countries listed under FMII. The study cover a ten (10) years period from 2008 until 2017. The study have shown significant relationship between inflation, money supply and exchange rate with FMII and managed to reject null hypotheses for the three variables. Inflation and exchange rate is negatively related with FMII while money supply, gross domestic product and oil price is positively related to FMII. However, the study fails to find any significant relationship between gross domestic product and oil price with FMII. The findings of this study will provide better understanding on the frontier market and helps to improve their performance. Therefore, it can encourage countries in frontier market to be able to compete and achieve similar advancement as countries in developed and emerging market did.